Design and rationale of a randomised controlled trial comparing apixaban to phenprocoumon in patients with atrial fibrillation on chronic haemodialysis: the AXADIA-AFNET 8 study. Issue 9 (10th September 2018) - Reinecke, Holger; Jürgensmeyer, Sabine; Engelbertz, Christiane; Gerss, Joachim; Kirchhof, Paulus; Breithardt, Günter; Bauersachs, Rupert; Wanner, Christoph
Abstract : Introduction: Patients with end-stage kidney disease requiring maintenance haemodialysis treatment experience a dramatic cardiovascular morbidity and mortality. Due to the high atherosclerotic and arteriosclerotic burden and profound alterations in haemostasis, they frequently suffer and die from both thromboembolic and bleeding events. This is a particular concern in patients on haemodialysis with atrial fibrillation (AF). Controlled trials on the optimal anticoagulation in patients with AF on haemodialysis are not available. The randomised controlled phase IIIb AXADIA–AFNET 8 trial will evaluate the safety and efficacy of the factor Xa inhibitor apixaban in patients with AF requiring haemodialysis. Methods and analysis: A total of 222 patients will be randomised in an open-labelled, 1:1 design to receive either apixaban 2.5 mg twice daily or dose-adjusted vitamin K antagonist therapy (target international normalised ratio 2.0–3.0). All patients will be treated and followed up for a minimum of 6 months up to a maximum of 24 months. The primary outcome is major or clinically relevant, non-major bleedings or death of any cause. Secondary outcomes include stroke, cardiovascular death and other thromboembolic events, thus exploring the efficacy of apixaban. The first patient was randomised in June 2017. Ethics and dissemination: The study protocol was approved by the Ethical Committee of the Landesaertzekammer, Westfalen-Lippe and the Medical Faculty of the University of Muenster, Muenster, Germany (reference number: 2016-598 f-A). Written informed consent will be obtained from all patients prior to study participation, including their consent for long-term follow-up. AXADIA–AFNET 8 is an investigator-initiated trial. Sponsor is AFNET, Muenster, Germany. Study findings will be disseminated to Bristol-Myers Squibb, Munich, Germany, and Pfizer, Berlin, Germany, to the participating centres, at research conferences and in peer-reviewed journals. Trial registration numbers: NCT02933697, Pre-results.